GE14 & Its Aftermath - Enter Malaysia’s New Political Order - Yang Razali Kassim (2018)
Days after the political earthquake of a general election on 9 May, Anwar Ibrahim declared Malaysia “on the verge of a new golden era”. Will it be a mere change of government or a political transition to a new order?